Cover Feature: AquaMMapS: An Alternative Tool to Monitor the Role of Water Molecules During Protein–Ligand Association (ChemMedChem 6/2018). (25th March 2018) - Cuzzolin, Alberto; Deganutti, Giuseppe; Salmaso, Veronica; Sturlese, Mattia; Moro, Stefano
Abstract : The Cover Feature shows the different behavior of structural water molecules and bulk water. We have developed the AquaMMapS tool, which is able to identify stationary hydration sites close to the protein surface starting from molecular dynamics simulation. Root‐mean‐square fluctuation (i.e., a 1.4 Å cutoff) is employed to discriminate stationary from nonstationary water molecules. Space is organized into a grid, where cells crossed by stationary water molecules are selected and their occupancy computed along the simulation. Moreover, an empirical scoring function, the AquaMMapScore, has been developed to evaluate the penalty of a ligand displacing a stationary water hot spot. More information can be found in the Full Paper by Stefano Moro et al. onpage 522 in Issue 6, 2018 (DOI:10.1002/cmdc.201700564 ).